Identificação de fatores de sucesso para a extubação em recém-nascidos prematuros - Thalita Vilaboim Santos (2023)
Introduction: Prematurity is birth before 37 completed weeks of gestation. It is related to high rates of mortality and morbidity among premature newborns. The immaturity of the organs and systems can lead to the need for the use of invasive mechanical ventilation, a support that is related to several deleterious effects, such as bronchopulmonary dysplasia. Methods, such as the spontaneous breathing test, and other indicators for assessing readiness for extubation in neonatology are not yet fully supported in the literature and studies are needed to identify factors related to the success of extubation in premature newborns. Objectives: To identify the sensitivity and specificity of the spontaneous breathing test in preterm infants and to evaluate and correlate pre-extubation clinical variables with extubation, identifying success factors for extubation other than the spontaneous breathing test. Methodology: This is a retrospective diagnostic study of data collection from medical records of a large public maternity hospital in Belo Horizonte, Hospital Sofia Feldman. All premature infants born alive between 2019 and 2020 who required invasive mechanical ventilation and underwent the spontaneous breathing test before extubation were selected. Results: After exclusion criteria, data from 218 medical records were analyzed, of which 195 (89.44%) were successful in SBT and were extubated, of which 161 (82.56%) were successfully extubated. On average, the individuals had a gestational age of 30 weeks, most of them males (61.5%), with a mean weight at extubation of 1456.1  681.4gr. The number of individuals who failed the ERT was 23 (10.55%) and of those who were successful in the ERT but failed in extubation was 34 (17.43%). If one considers that all 23 cases of ERT failure were not even submitted to extubation, therefore they would be counted as extubation failure, the ERT would be shown to be a test of very high sensitivity (100%) and low specificity (40.4%), with AUC = 0.70; 95%CI: 0.61 to 0.79; p-value: <0.001. The binomial regression model showed that the predictive variables for successful extubation were: weight at extubation OR: 1.02 (95%CI: 1.01 to 1.04), PaCO2 OR: 0.93 (95%CI: 0.89 to 0.98) and heart rate OR: 0.97 (95%CI: 0.94 to 0.99), with a sensitivity of 85.91% (95%CI: 79.27 to 91.06%), specificity of 63.64% (95%CI: 30.79 to 89.07%). PaCO2 and HR were able to discriminate the cutoff points for extubation success x failure: 34.7 mmHg for PaCO2 and 156 bpm for HR (Wilks's Λ = 0.955 and 0.932; 2(gl=1) = 7.30 and 13.10; p=0.007 and <0.001). Conclusion: The present study found diagnostic sensitivity and specificity values of the spontaneous breathing test and demonstrated a predictive relationship of the extubation outcome with simple variables that are present in the routine of neonatal ICUs, PaCO2 and HR. In addition, we found PaCO₂ and HR cutoff points that are discriminatory in predicting extubation success or failure.